2018
DOI: 10.5194/isprs-archives-xlii-1-355-2018
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Visual Localization in Outdoor and Indoor Environments Exploiting 3d Image Spaces as Spatial Reference

Abstract: <p><strong>Abstract.</strong> In this paper, we present a method for visual localization and pose estimation based on 3D image spaces. The method works in indoor and outdoor environments and does not require the presence of control points or markers. The method is evaluated with different sensors in an outdoor and an indoor test field. The results of our research show the viability of single image localization with absolute position accuracies at the decimetre level for outdoor environments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sattler et al (2018) distinguish the following visual localization categories: 3D structure-based, 2D image-based, sequence-based and learningbased localization. In our previous work, we introduced a method for visual localization and pose estimation of a single image to georeferenced RGB-D images (Nebiker et al, 2015;Rettenmund et al, 2018). This method works in indoor and outdoor environments and does not require ground control points.…”
Section: Related Workmentioning
confidence: 99%
“…Sattler et al (2018) distinguish the following visual localization categories: 3D structure-based, 2D image-based, sequence-based and learningbased localization. In our previous work, we introduced a method for visual localization and pose estimation of a single image to georeferenced RGB-D images (Nebiker et al, 2015;Rettenmund et al, 2018). This method works in indoor and outdoor environments and does not require ground control points.…”
Section: Related Workmentioning
confidence: 99%
“…Sattler et al (2018) distinguish the following visual localization categories: 3D structure-based, 2D image-based, sequence-based and learningbased localization. In our previous work, we introduced a method for visual localization and pose estimation of a single image to georeferenced RGB-D images (Nebiker et al, 2015;Rettenmund, Fehr, Cavegn, & Nebiker, 2018). This method works in indoor and outdoor environments and does not require ground control points.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to database updating and asset management, there is a high demand for real-time device pose estimation for augmented reality applications, where 3D image spaces have a great potential for serving as reference data. First investigations of visual localization using 3D image spaces showed that large temporal differences and the associated changes in scene content and appearance are one of the main challenges in long-term visual localization (Rettenmund et al, 2018).…”
Section: Introductionmentioning
confidence: 99%